Factors Contributing to Lingering Pain after Surgery: The Role of Patient Expectations. (June 2021) - Willingham, Mark D.; Vila, Molly R.; Ben Abdallah, Arbi; Avidan, Michael S.; Haroutounian, Simon
Abstract : Background: Pain that lingers beyond the early weeks after the acute postoperative period is an important risk factor for chronic postsurgical pain. This study examined the hypothesis that patients' expectations about their postsurgical pain would be independently associated with lingering postsurgical pain. Methods: The study included 3, 628 patients who underwent diverse surgeries between February 2015 and October 2016 in a single U.S. tertiary hospital and participated in the Systematic Assessment and Targeted Improvement of Services Following Yearlong Surgical Outcomes Surveys (SATISFY-SOS) observational study. Preoperatively, patients were asked about their expectations about pain 1 month after surgery. Patients were considered to have lingering postsurgical pain if they endorsed having pain in the area related to their surgeries during a follow-up survey obtained 1 to 3 months postoperatively. The independent associations between preselected perioperative variables and lingering postsurgical pain were evaluated. Results: Of the cohort, 36% (1, 308 of 3, 628) experienced lingering postsurgical pain. Overall, two thirds (2, 414 of 3, 628) expected their postsurgical pain to be absent or improved from baseline, and 73% of these had their positive expectations fulfilled. A total of 19% (686 of 3, 628) expected new, unabated, or worsened pain, and only 39% (257 of 661) of these had their negative expectations fulfilled. Negative expectations were most common in patients with presurgical pain unrelated to the reason for surgery, undergoing surgeries not typically performed to help alleviate pain. Endorsing negative expectations was independently associated with lingering postsurgical pain (odds ratio, 1.56; 95% CI, 1.23 to 1.98; P < 0.001). Additional major factors associated with lingering postsurgical pain included recollection of severe acute postoperative pain (odds ratio, 3.13; 95% CI, 2.58 to 3.78; P < 0.001), undergoing a procedure typically performed to help alleviate pain (odds ratio, 2.18; 95% CI, 1.73 to 2.75; P < 0.001), and preoperative pain related to surgery (odds ratio, 1.91; 95% CI, 1.52 to 2.40; P < 0.001). Conclusions: Lingering postsurgical pain is relatively common after diverse surgeries and is associated with both fixed surgical characteristics and potentially modifiable factors like pain expectations and severe acute postoperative pain. Abstract : In a single-center cohort of 3, 628 patients undergoing a broad range of surgeries, 36% experienced lingering pain. Factors associated with lingering pain include negative expectations of pain, preoperative pain related to the surgery, recollection of severe acute postoperative pain, and undergoing a procedure typically performed to help alleviate pain.Supplemental Digital Content is available in the text.